Joyful infographics : a friendly, human approach to data - Holmes, Nigel, 1942- (Boca Raton : AK Peters, CRC Press, 2023)
"In Joyful Infographics, one of the leading graphic designers of recent times shows how a judicious use of humor can make infographics more understandable. Written in non-academic, easy to understand language, and with historical and contemporary visual examples presented throughout, this small book provides a short history of light-hearted graphics; it outlines eight clear ways to make graphics more understandable; it explores the importance of the audience; it shows you how to make information come alive during presentations through live-action 'performance' graphics; it discusses why joy and smiling are good for you; and it shows you how not to overdo it. Even if a subject is delicate, controversial, or taboo, being graphically friendly to the audience is the right way to explain it. It is the opposite of being clinically cold and just presenting the facts. If you can get readers to smile - the smile of recognition when they understand the graphic - you are more than halfway towards getting them to continue reading, and understanding, the intention of the piece. Joyful Infographics teaches you how to do just that"--
Warming up -- Introduction -- Influences -- Pictorial data through the ages -- Nine ways to make your graphics joyful -- icons -- Joyful presentations -- Science -- Chartoons and jokes -- Don't do this!
OCLC-licensed vendor bibliographic record.
Keywords: Information visualization; Graphic arts; Caricatures and cartoons; COMPUTERS / Computer Graphics / General